Processing and characterization of graphene nano-platelet (GNP) reinforced aluminum matrix composites - Akçamlı, Nazlı; Gokce, Hasan; Uzunsoy, Deniz (Carl Hanser Verlag, 2016)
Aluminum matrix composites containing graphene nanoplatelets (GNPs) as reinforcement additive were fabricated by a two-step process consisting of mechanical alloying and pressureless sintering. The effects of graphene nano-platelets amounts and mechanical alloying duration on the microstructural and mechanical properties of aluminum were investigated. The characterization studies were performed by X-ray diffractometry, Raman spectroscopy, scanning electron microscopy/energy dispersive spectrometry, particle size analysis, differential scanning calorimetry, Archimedes' density and microhardness test method. The microhardness of composites increased gradually by the addition of 0.5 and 1 wt.-% GNP, whereas an adverse effect was observed by the increment of the GNP amount to 2 wt.-%.
Keywords: Aluminum matrix composites; graphene nano-platelet (GNP); mechanical alloying; microstructure; mechanical properties